ERS International Congress, Madrid, 2019: highlights from the Interstitial Lung Diseases Assembly - Dupin, Clairelyne; Fernandes, Vânia; Hernandez-Gonzalez, Fernanda; Torrisi, Sebastiano Emanuele; Alfaro, Tiago M.; Kreuter, Michael; Wijsenbeek, Marlies S.; Renzoni, Elisabetta A.; Bargagli, Elena; Nunes, Hilario; Spagnolo, Paolo; Bonella, Francesco; et al. (ERJ Open Research, 2020)
This article discusses a selection of the scientific presentations in the field of interstitial lung diseases (ILDs) that took place at the 2019 European Respiratory Society International Congress in Madrid, Spain. There were sessions from all four groups within Assembly 12: group 12.01 “Idiopathic interstitial pneumonias”, group 12.02 “ILDs/diffuse parenchymal lung diseases (DPLDs) of known origin”, group 12.03 “Sarcoidosis and other granulomatous ILDs/DPLDs” and group 12.04 “Rare ILDs/DPLDs”. The presented studies brought cutting-edge developments on several aspects of these conditions, including pathogenesis, diagnosis and treatment. As many of the ILDs are individually rare, the sharing of experiences and new data that occur during the Congress are very important for physicians interested in ILDs and ILD patients alike.
Gesehen am 31.03.2025